Respuesta :

Answer:

[tex]x=5,y=4[/tex]

Step-by-step explanation:

[tex]2x-3y=-2[/tex]

Add 3y to both sides:

[tex]2x-3y+3y=-2+3y[/tex]

[tex]2x=-2+3y[/tex]

Divide both sides by 2:

[tex]\frac{2x}{2}=-\frac{2+3y}{2}[/tex]

[tex]x=\frac{-2+3y}{2}[/tex]

Substitute this into the second equation:

[tex]4* \frac{-2+3y}{2}+y=24[/tex]

[tex]2\left(3y-2\right)+y=24[/tex]

[tex]7y-4=24[/tex]

Add 4 to both sides:

[tex]7y-4+4=24+4[/tex]

[tex]7y=28[/tex]

Divide both sides by 7:

[tex]\frac{7y}{7}=\frac{28}{7}[/tex]

[tex]y=4[/tex]

We know that [tex]x=\frac{-2+3y}{2}[/tex]

Thus, [tex]x=\frac{-2+3* \:4}{2}[/tex]

[tex]x=\frac{10}{2}[/tex]

[tex]x=5[/tex]

Answer:

using elimination rule

multiply equation 2 by 3

we get, 12x+3y=72

now solve both equation

2x-3y= -2

(+)12x+3y=72

-----------------

14x=70

x=70/14=5

put value of x in any of the equation y=4

mark its as brainliest!!!!